(3GdEbJUGO hGdeGd aj GdJTQjY GdESdGej hGdfXe GdhVYjI (B:s (3HMhK hCMGOjK hOQGSGJ ebGQfI (B/s - (3YWhj, ahRjs ((3HjQhJ(B: s (3OGQ GdacQ GdYQHj(B, s, 1988)
(3GdeTcdI GdGbJUGOjI hacQI GdeSDhdjI,GdHMhK GdESdGejI aj GddZGJ GdCLfHjI,GdLhGfH GdGbJUGOjI ddRcGI,GdGfUGa aj GdfXGe GdeGdj GdESdGej,GdehGQO GdeGdjI bHd GdESdGe,GdehGQO GdeGdjI aj GdESdGe,GdebGQfI Hjf VQGFH GdESdGe hGdCOjGf GdCNQi,Gdhba hGdejQGK hGdhUjI aj GdESdGe,GdQHG hGdaGFOI hGdfXGe GdeUQaj,GdESdGe heYGdLI GdabQ,GdfbhO aj GdBKGQ GdESdGejI hGdYQHjI,JWhQ GdfbhO GdYQHjI hGdESdGejIs
(3HHdjhZQGajG(B:(3U(B.151-156s
Keywords: (3GdGbJUGO GdGSdGejs